2018
DOI: 10.1186/s41935-018-0038-x
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium glutamate affects cognitive functions in male albino rats

Abstract: Background: Monosodium Glutamate is a silent toxin in our food, especially our kids' food. Some of the products in the market contain MSG in a level exceed the European limit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Increased IL-6, resistin, and tumor necrosis factors in adipose tissues are the primary effects of MSG on body weight. The elevated serum levels of resistin and insulin can deteriorate the visceral adipose tissue [59]. Additionally, the ingestion of MSG has a local effect.…”
Section: Discussionmentioning
confidence: 99%
“…Increased IL-6, resistin, and tumor necrosis factors in adipose tissues are the primary effects of MSG on body weight. The elevated serum levels of resistin and insulin can deteriorate the visceral adipose tissue [59]. Additionally, the ingestion of MSG has a local effect.…”
Section: Discussionmentioning
confidence: 99%
“…Wafaa M. et al (2018) demonstrated that giving MSG in low doses caused the male albino rats to gain weight. In addition to changes in brain [28].…”
Section: The Effect Of Msg On Food Intake Obesity and Body Immunitymentioning
confidence: 99%
“…High exposure to MSG represents a major health problem in Egypt, as it is found in a large number of food products; especially those directed to kids, within levels exceed the European limit of 10 g/kg (1%) of product. Even if found within the allowable limits in some food products, the over and repeated consumption of these products per day without paying attention to the total amount of MSG ingested exposes the person to critical health challenges in the next years (Abdel Moneim et al, 2018). This study was carried out to investigate the weight control and hepato-renal protective effects of Spirulina in MSG -exposed female rats.…”
Section: Introductionmentioning
confidence: 99%